2014
DOI: 10.1007/s11095-014-1521-1
|View full text |Cite
|
Sign up to set email alerts
|

Could Albumin Affect the Self-Assembling Properties of a Block Co-polymer System and Drug Release? An In-Vitro Study

Abstract: Our results suggested that the kinetics of MTX release mainly depended on the presence of the thermogelling copolymer, although other mechanisms related to BSA could be involved. Finally, the study assessed the feasibility of using a thermogelling hydrogel for in situ drug administration in areas with the presence of high protein concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
3
7
0
Order By: Relevance
“…Since the K D value is the reciprocal of the association constant, the lower value of K D for complex 1 suggests a stronger binding ability as compared to complex 2 . These results are comparable to the binding constants of some biologically active molecules and anticancer drugs, indicating that the two complexes can be stored and released by BSA . Furthermore, from the above calculations, it is proposed that there is just one single binding site in BSA for both complexes.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Since the K D value is the reciprocal of the association constant, the lower value of K D for complex 1 suggests a stronger binding ability as compared to complex 2 . These results are comparable to the binding constants of some biologically active molecules and anticancer drugs, indicating that the two complexes can be stored and released by BSA . Furthermore, from the above calculations, it is proposed that there is just one single binding site in BSA for both complexes.…”
Section: Resultssupporting
confidence: 67%
“…Clearly, the two complexes can interact with different types of amino acid residues, which makes complexes 1 and 2 favorably select hydrophobic Trp213 and hydrophilic Trp134 sites, respectively. The information on the selection of the binding sites for the two complexes may be useful for understanding the metabolic mechanism for these kinds of complexes …”
Section: Resultsmentioning
confidence: 99%
“…Since the K D value is the reciprocal of the association constant, the lower value of K D for the complex 1 suggests a relatively stronger binding ability as compared to the complex 2. These results are comparable to the binding constants of some biologically active molecules and anticancer drugs [56,57], indicating that the present two complexes can be stored and released by the protein BSA [58]. The exact binding site in BSA for the two complexes is going to be determined by the following molecular docking calculation.…”
Section: A N U S C R I P Tsupporting
confidence: 65%
“…Copolymer blending is a type of polymer blending approach in which two or more block copolymers with different characteristics, functionalities, and stimuli-responsiveness are mixed in order to form a unique polymer blend with special characteristics (Keogh et al, 2020). It has been reported that recruitment of albumin in the synthesis of block copolymers could affect drug release profile from hydrogels, while the gel consistency of the fabricated block copolymer was reduced (Perinelli et al, 2014).…”
Section: Block Copolymersmentioning
confidence: 99%
“…In addition, it has been emphasized that although the gel consistency of the finalized block copolymer was reduced in the presence of BSA, the rate of drug release was also reduced in this condition. These results could be attributed to different mechanisms of drug release that BSA might be involved in other than the well-recognized drug dissolution and hydrogel erosion mechanisms (Perinelli et al, 2014). Using block copolymers that are composed of PEG and PLA polymers could result in the fabrication of novel drug delivery systems with desired drug release profiles.…”
Section: Block Copolymersmentioning
confidence: 99%